Attitude and practices of tracheostomy care among nursing staff in Saudi Arabia - Turki M. Bin Mahfoz (BMC, 2022)
Abstract Background In many regions of the world, tracheostomy care is a major health concern. Many patients die as a result of nurses' lack of awareness regarding tracheostomy care. This study was carried out to report the acquired training, clinical experience and team approach while caring for patients with tracheostomies and then evaluate these aspects on nurses' confidence in caring for these patients. Methods A cross-sectional descriptive study involving a self-administered questionnaire was carried out among nurses from October 2020 to June 2021. A self-administered questionnaire including questions on sociodemographic characteristics, tracheostomy training and support and confidence in caring for patients with tracheostomies. It was disseminated electronically to the nurses working in a tertiary medical center in Saudi Arabia with multiple reminders. Group difference was determined using t test and chi square tests appropriately with a set p value to less than 0.05. Results A total of 315 nurses with different educational backgrounds were included. The majority were females, middle aged and gained their nursing degree from outside the country. Over 30% of the nurses cared for patients with tracheostomies while more than two thirds did not receive adequate training to care for this patient population. Confidence was reflected in the working units, the time spent caring for these patients and the number of patients cared for. Additionally, nurses caring for children and adults with tracheostomies were more confident in their care than those caring for adolescents and older adults. Conclusion Continuous training and competency evaluation are vital in delivering optimal care. Confidence level is impacted by training received and by the presence of assisted ventilation. Future studies should aim for a national representation of this topic to inform policy and practice.